Cabaran dan amalan perubahan terancang di sekolah bestari: penggunaan SSMS sebagai teknologi instruksional dalam pengajaran dan pembelajaran - Mohd Hamzah, Mohd Izam; Hussin, Sufean (UUM College of Arts and Sciences, 2007)
This article discusses the practice of using the Smart School Management System(SSMS) as an instructional technology medium in teaching and learning in Malaysian smart schools. Data was gathered through observation and interviews. The findings indicate that in the teaching and learning process, teachers focus on network applications such us the internet or SSMS, appropriateness and teamwork characteristics, and equal access for quality learning. However, emotional stability and global orientation are not emphasize. The study also shows that diferent levels of learning were not practiced in all subjects, nor implemented at all schools. In relation to the use of SSMS, several problems occured such as technical dificulties,the existence of two different syllabuses, student number exam-orientedness,assesment validity and excessive teacher workload.In addition, there were problems with regard to the teaching and learning material including factual errors, quality control and mismatches with syllabus and student ability. Several suggestions are proposed to overcome these problems, among them: increeasing the number of computer technicians in smart schools, upgrading the network at smart schools, implementing only the smart school syllabus for teaching and learning, setting the maximum number of students in a class at 36,focusing on non- examination purposes,increasing the number of computers at B and B+ level smart schools, expanding into other subject areas, ensuring a balanced workload among teachers, and increasing the quality of teaching and learning material for diverse learners.